Empathy and exclusion in the design process - Marsden, Nicola; Wittwer, Alexander (Frontiers in Human Dynamics, 2022)
Designers are now taught that empathy with users is crucial to technology design. We offer a warning that this dictum and its implementation, despite admirable intentions, can promote exclusion in design: Empathy will not bring the desired benefit to the design process if it is naively construed and understood as a feminine trait, if shortcuts are used to allegedly take the effort out of the empathic process, or if the social situation in which empathy is taking place is not considered. We show that these issues are closely coupled in design practices. Using personas—fictitious descriptions of people used to make users visible in the design process—as an example, we argue that the danger of reifying gendered assumptions might be inherent in those methods and tools in human-computer interaction research that are supposed to enable and strengthen empathy.